2020
DOI: 10.34172/ijhpm.2020.249
|View full text |Cite
|
Sign up to set email alerts
|

Using Group Model Building to Capture the Complex Dynamics of Scaling Up District-Level Surgery in Arusha Region, Tanzania

Abstract: Background: Scaling up surgery at district hospitals (DHs) is the critical challenge if the Tanzanian national Surgical, Obstetric, and Anesthesia Plan (NSOAP) objectives are to be achieved. Our study aims to address this challenge by taking a dynamic view of surgical scale-up at the district level using a participatory research approach. Methods: A group model building (GMB) workshop was held with 18 professionals from three hospitals in the Arusha region. They built a graphical representation of the local sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Our earlier paper involving application of a systems dynamics tool (Group Model Building) revealed that scale-up requirements are complex and resource intensive [ 43 ]. National Surgical, Obstetric and Anaesthesia Plans (NSOAPs), recently adopted and currently being implemented in Tanzania [ 44 ] and Zambia [ 45 ] are widely considered as charting the right direction for surgical scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier paper involving application of a systems dynamics tool (Group Model Building) revealed that scale-up requirements are complex and resource intensive [ 43 ]. National Surgical, Obstetric and Anaesthesia Plans (NSOAPs), recently adopted and currently being implemented in Tanzania [ 44 ] and Zambia [ 45 ] are widely considered as charting the right direction for surgical scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…What we hope to contribute are practical questions to guide the earliest stages of this process. These may suggest the need for more specific, formal codesign strategies 40 41 51. Unfortunately, funding models for such codesigned research approaches are uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with our earlier study, which reported particularly poor utilisation of operating theatres in Zambia, at around 10% of capacity [ 35 ]. Zambia recently launched a national programme to build an additional 115 ‘mini hospitals’, with bed capacities of 80 and an operating theatre to perform basic surgery [ 41 ]. Our findings suggest that this may not be the most efficient approach to meeting the needs of dispersed rural populations.…”
Section: Discussionmentioning
confidence: 99%